Ichthyoarchaeological perspectives on roles of fish and red meat during Indus Civilization in Gujarat, India - Abhayan, G. S.; Joglekar, Pramod P.; Ajithprasad, P.; Rajesh, S. V.; Goyal, Pankaj; Chase, Brad; Kharakwal, Jeevan; Shirvalkar, Prabodh (Frontiers in Environmental Archaeology, 2025)
The roles of animals during the Indus Civilization (circa 4000 BCE to 1300 BCE), which thrived in South Asia, have been extensively studied by zooarchaeologists. While significant progress has been made in understanding the domestication and hunting of mammals, information on the use of aquatic organisms such as fish, mollusks, and crustaceans has been relatively sparse. Excavations at Indus Civilization sites have uncovered substantial quantities of fish remains, potentially providing valuable insights. In South Asia, the study of fish remains has often been neglected, primarily due to the lack of comprehensive reference collections for comparison. This paper discusses the current state and future possibilities of South Asian ichthyoarchaeology, highlighting the results of ichthyoarchaeological investigations in the Gujarat region of India. Analysis of fishbone assemblages from Indus sites such as Bagasra, Kanmer, Shikarpur, Kotada Bhadli, and Navinal in Gujarat has identified 24 fish species from 14 families. Evidence of anthropogenic activities such as cut marks, charring, and chewing on the bones suggests various aspects of fish consumption. These analyses reveal information about the diversity of fish species used, fishing environments, changes in fish consumption across different cultural phases, spatial distribution of fish remains within the sites, and fish processing patterns. The ichthyoarchaeological data aligns with cultural changes inferred from archaeobotanical and non-fish faunal records from these sites. This paper offers insights into a more nuanced role of fish in the diet, tailored to the tastes and preferences of consumers, rather than being a secondary or incidental food source, alongside mammalian meat during the Harappan Civilization in the Gujarat region.